PENGARUH LINGKUNGAN KELUARGA, SOSIO-PSIKOLOGI, DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR - Rohimah, Siti; Suriswo, Suriswo; Nugroho, Rahmad Agung (Elementar : Jurnal Pendidikan Dasar, 2025)
This study aims to determine the influence of family environment, socio-psychology and learning motivation on Mathematics learning outcomes. The research sample was 135 students from 203 students in grade IV of Public Elementary Schools in Dabin 3 KWK Ampelgading Pemalang Regency with proportional random sampling technique. The source of research data used was primary data obtained directly from respondents with a questionnaire. The data processing tool used was SPSS for windows version 21. Data analysis used multiple linear regression analysis. From the data test and analysis conducted, this study provides empirical evidence as follows: family environment, socio-psychology and learning motivation have a positive and significant effect on Mathematics learning outcomes.